2008
DOI: 10.1007/bf03176156
|View full text |Cite
|
Sign up to set email alerts
|

Textural and compositional evidence for the evolution of pedogenic calcite and dolomite in a weathering profile on the Kohala Peninsula, Hawai’i

Abstract: Pedogenic dolomite and high magnesium calcite (HMC) occur as micritic matrix and void filling microspar in soils developed on semi-arid 350 Ka basalt surfaces on Hawai'i Island. The void filling carbonate presents an unusual appearance of alternating concentric < 5 urn to -30 um layers ofHMC and dolomite at shallow (100 cm) depths and similar layers that are exclusively dolomite between depths of 170 em and 350 em. Elevated Mg/Ca ratios in soil water, caused by rapid basalt weathering, likely provided geochemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…For disordered, Ca-rich dolomite to form, Folk and Land [1975] proposed that an Mg/Ca ratio >1 is required, but others have suggested that values as high as 3.31 are required [Hardie, 1987]. In Hawaiian soil, dolomite develops on basalt and precipitates when the Mg/Ca ratio of its soil solution is $1 [Capo et al, 2000;Whipkey and Hayob, 2008;Whipkey et al, 2002]. Stream flux on central CLP has a Mg/Ca ratio of 2.34 and the largest river on CLP, the Yellow River has an Mg/Ca ratio of $0.85 Zhang et al, 1995].…”
Section: Formation Of Red Clay Protodolomitementioning
confidence: 99%
“…For disordered, Ca-rich dolomite to form, Folk and Land [1975] proposed that an Mg/Ca ratio >1 is required, but others have suggested that values as high as 3.31 are required [Hardie, 1987]. In Hawaiian soil, dolomite develops on basalt and precipitates when the Mg/Ca ratio of its soil solution is $1 [Capo et al, 2000;Whipkey and Hayob, 2008;Whipkey et al, 2002]. Stream flux on central CLP has a Mg/Ca ratio of 2.34 and the largest river on CLP, the Yellow River has an Mg/Ca ratio of $0.85 Zhang et al, 1995].…”
Section: Formation Of Red Clay Protodolomitementioning
confidence: 99%
“…The setting of formation of these dolomite-rich calcretes is different of those commonly described as a result of the evolution of groundwater to reach evaporitic conditions in terminal basin settings (Colson and Cojan, 1996;Jutras et al, 2011;Jutras, 2017) or as a result of the emerging groundwater also under evaporitic conditions (Mather et al, 2019). The scarce spheroidal dolomite found mostly cementing voids of the volcanic fragments is probably the first dolomite phase formed, as in Mirador del Rio profile in Lanzarote, where the initial weathering of the basalts could produce locally enriched Mg-solutions favoring dolomite formation (Capo et al, 2000;Whipkey et al, 2002;Whipkey and Hayob, 2008) as a cement (Alonso-Zarza et al, 2016).…”
Section: Calcrete Profiles Interpretationmentioning
confidence: 76%